Structuration Analysis of the Transition of St. Paul University Tuguegarao, Philippines from College to University - Evardone, Salvador (JPAIR Multidisciplinary Research, 2015)
The school established by the Congregation of the Sisters St. Paul of Chartres (SPC) in Tuguegarao had grown from its school opening in 1907 up to its expansion to college in 1949. It gave the town a Catholic education imbued with Paulinian charism. Their missions and objectives responded effectively to the needs of the time. The purpose of this study is to write the history of the transition of St. Paul school in Tuguegarao from college to university. It will attempt to recount the significant transformation of this academic institution by utilizing the Structuration Theory of Anthony Giddens as its theoretical framework. It also employed the method of oral history through interviews supplemented and corroborated by the data retrieved in the archives. The time-space element in this study is the transition of St. Paul University Tuguegarao from 1949 to 1982. From the onset, St. Paul College Tuguegarao (SPCT) had established constant communication among the administrators, faculty, staff, and students for stability, alignment to vision-mission and relevance to society. Since its attainment of college status in 1949, more courses were offered, and facilities were added. Such endeavors necessitated numerous meetings, deliberations, and assessments that led the school to a transition from college to university in 1982.